Climate Change Mitigation Towards the Lens of Urban Heat Island under Urban Forest Development - Rushayati, Siti Badriyah; Nur Annisa, Namira; Setiawan, Yudi; Condro, Aryo Adhi (Jurnal Sylva Lestari, 2025)
Rapid urbanization and land-use change in Indonesian cities have led to urban heat islands, exacerbating air pollution. This situation elevates sensible heat, thereby compromising human thermal comfort. Palu City, situated in Central Sulawesi Province, Indonesia, has experienced significant urban heat island effects in recent decades. To mitigate this issue, increased development of green open spaces is necessary. This study prioritizes urban forest development in urban areas using a spatial analysis approach. We employ a weighting and scoring system based on vegetation indices, land cover, and air temperature parameters. Our study identified three priority areas with total areas of approximately 6,741 ha, 2,746 ha, and 20,695 ha for priorities 1, 2, and 3, respectively. This study prioritizes areas with high temperatures, low vegetation cover, and bare land for urban forest development. To effectively implement the proposed urban forest development plan, this study also highlights recommendations to create a more sustainable, resilient, and livable urban environment. Keywords: climate change, Landsat-8, micro-climate, remote sensing, urban forest, urban heat island